1994
DOI: 10.1159/000263949
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Pathophysiology, and Treatment of Chronic Twin-to-Twin Transfusion Syndrome

Abstract: The discovery of a ‘stuck twin’ during an ultrasound examination has often been equated with twin-to-twin transfusion based to a great extent on postnatal confirmation of discordant fetal size and hemoglobin concentration. However, the diagnosis of twin-to-twin transfusion cannot be made with certainty after birth since virtually all monochorionic gestations have placental anastomoses and there are many causes of growth deficiency and abnormal hemoglobin concentration. The purpose of this study is to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 10 publications
0
35
0
3
Order By: Relevance
“…Elliot et al [21] suggested that amniocentesis decreases amniotic fluid pressure resulting in reversal or stabilization of blood transfer between the twins and improved placental perfusion. Weiner and Ludomirski [2] and Meagher et al [25] measured amniotic fluid pressure prior to therapeutic amniocentesis and found it increased when compared with normal pregnancies. The pressure decreased following reduction amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elliot et al [21] suggested that amniocentesis decreases amniotic fluid pressure resulting in reversal or stabilization of blood transfer between the twins and improved placental perfusion. Weiner and Ludomirski [2] and Meagher et al [25] measured amniotic fluid pressure prior to therapeutic amniocentesis and found it increased when compared with normal pregnancies. The pressure decreased following reduction amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…By the eleventh day after amniocentesis, the amniotic fluid in both sacs had normalized and remained as such until delivery at 35 5 / 7 weeks. The sudden resolution of the syndrome after one or more amniocenteses, and the failure to document an increase in urine production in the stuck twin in the few cases where it was measured [2,24], are not consistent with the explanation that the postprocedural increase in the amniotic fluid around the stuck twin is always the direct result of improved fetal renal perfusion. We propose that, in cases where resolution of the syndrome occurred unexpectedly, the amnion separating the twins was inadvertently punctured at the time of amniocentesis.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Blizanci koji se u drugom trimestru prezentuju sa teškim TTTTS, mogu imati hemodinamski disbalans u prvom trimestru, koji se manifestuje kao diskordantna povećana nuhalna translucenca (NT) u 10. do 14. nedelji gestacije [13]. Ovo je od značaja, jer je NT primarno screening za aneuploidije u multiploj trudnoći.…”
Section: Predikcija Ttttsunclassified
“…Ovo se vidi kod 32% MC trudnoća, a od njih će 43% kasnije razviti TTTTS [13]. Međutim, upotrebljivost ovih subjektivnih nalaza u predikciji TTTTS ostaje diskutabilna [39].…”
Section: Predikcija Ttttsunclassified